The Effects of Leverage, Executive Characters, and Institutional Ownership to Tax Avoidance with Political Connection as Moderation - Maharani, Fifi Setya; Baroroh, Niswah (Accounting Analysis Journal, 2019)
This study aims to examine the effects of leverage, executive character, and institutional ownership on tax avoidance with political connection as a moderating variable. The population was 48 mining companies listed in the Indonesia Stock Exchange during the period of 2014-2017. The sampling method was a purposive sampling method and selected 52 units of analysis from 14 companies. Analysis of research data used descriptive statistics and inferential statistics. The hypothesis testing used moderating regression analysis with an absolute difference test. The results show that leverage has a significant negative effect while executive character and institutional ownership have no effect on tax avoidance. Then, political connection significantly moderates the effect of leverage and executive character but it does not significantly moderate the effect of institutional ownership on tax avoidance. The conclusion of this research is only leverage which has an effect on tax avoidance and political connection only moderates the effect of leverage and executive character on tax avoidance.